The Old: Is There Any Role for Screening Colonoscopy after the Age of 75? The Surgeon's Perspective - Khan, Imran; Belkovsky, Mikhael; Gorgun, Emre (Clinics in Colon and Rectal Surgery, 2024)
Guidelines recommend individualized decision making for screening colonoscopy for colorectal cancer (CRC) in patients after the age of 75 years due to low additional benefits. That should be taken with a grain of salt, as these recommendations are based on expert opinion and simulation models which do not consider (1) the differences in pathogenesis and cancer biology of CRC in elderly; (2) the risks of colonoscopy in this patient population; (3) and the impact of new surgical and nonsurgical therapies for CRC. In this review, our goal is to bring a surgeon's perspective to understand the role of screening colonoscopy in patients older than 75 years.
Keywords: elderly patient; frailty; geriatric population; screening colonoscopy; colorectal cancer; quality of life